Nature of water bonding in hydrated milk-protein systems - Goncharuk, Elena; Polishchuk, Galyna; Shevchenko (Kishenko), Iryna; Osmak (Fedchenko), Tetiana (My University, 2020)
The nature of the connection and the characteristics of the process of relaxation of clusters and water domains in milk and protein systems was investigated in order to predict their functional and technological properties. Досліджено характер зв’язку та характеристики процесу релаксації кластерів і водних доменів у молочно-білкових системах з метою прогнозування їх функціональних та технологічних властивостей.
Keywords: milk; protein; concentrate; молоко; білок; концентрат; кафедра технології молока і молочних продуктів; кафедра технології м’яса і м’ясних продуктів